PERANCANGAN IKLAN SAMBAL GAMI RUMINI KALIWUNGU DENGAN TEKNIK NATIVE AUTOPLAY ADS - Nadya Yulia Sawitri; Edy Siswanto; Dendy Kurniawan (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
This study aims to design a digital advertising strategy for the local product *Sambal Gami Rumini* from Kaliwungu by utilizing native autoplay ads as an effective promotional method on social media. The main focus is to create advertising content that integrates naturally into users’ media consumption without disrupting their experience, thereby attracting attention organically. The design process employed a qualitative approach through observation, interviews, and literature study to gain a deeper understanding of the product characteristics, target audience, and appropriate distribution media. The choice of native autoplay ads was based on its ability to deliver messages smoothly through automatically played videos, without requiring initial user interaction, thus increasing engagement potential. The results of this study are expected to produce an attractive and adaptive visual communication solution that not only enhances the appeal of a local culinary product but also expands the digital market reach of *Sambal Gami Rumini*.